Nutrition in the HIV response of Homa Bay County, Kenya between 2014 and 2018 - Onyango, Susan Atieno; ADAMU, VE; Okomo, G. O.; Oketch, F. A. (Orapuh Journal, 2020)
Introduction Nutrition therapy is now strongly advocated to be integrated into Antiretroviral Therapy (ART). Nutrition interventions aim to prevent malnutrition and restore nutritional status to maintain PLHIV’s productivity. In Kenya, the Food by Prescription (FBP) program provides nutritional support to malnourished PLHIV. Homa Bay County has been implementing nutrition support services for PLHIV since the advent of devolution of counties. Purpose The purpose of this study was to assess selected nutrition indicators in the HIV response of Homa Bay County, Kenya between 2014 and 2018. Materials and methods Data were extracted from the Kenya Health Information System (KHIS), using a data sheet, analysed, and studied. The indicators selected for this study included: number of clients assessed for malnutrition, eligibility for food support, treatment outcomes for PLHIV on food support, reporting rates, and nutrition commodities stockouts. Data obtained from the survey were analysed using descriptive statistics. Some of the results were also presented in tables as frequencies or frequencies and percentages. Results Results of the study indicated that 15% to 65% of adults attending the HIV/ AIDS clinics in public health facilities were malnourished, while 30% of children attending the clinic were also malnourished. The number of patients assessed for malnutrition increased from 1,742 in 2014 to 133,880 in 2018 while those who received food support increased from 2,702 to 17,116. Reporting rates for nutrition services and nutrition commodities increased from 12% and 16.3% respectively to 99% for both. Nutrition commodity stock out days reduced from 349 days and 200 days for therapeutic and supplementary foods respectively to 40 days and 20 days. Cure rates were still found to be low at 20% against the recommended 75%. Conclusion The county needs to strengthen the systems, including the channels through which they receive nutrition commodities.